Development of Package Identification System (PIS) for Bustel Klebang with Decision Support System (DSS) features / Shahira Rohaiza Sakrani - Sakrani, Shahira Rohaiza (2015)
This research was about Design of Package Identification System (PIS) for Bustel Klebang with Decision Support System (DSS) features. Bustel Klebang Melaka is placed in Dataran 1Malaysia, Klebang Besar at Malacca state. Bustel Klebang has operate on Jun 2014. Currently, this Bustel does not have any computerize system and all the information have been recorded manually. Also there is still no website exist for booking reservation by online. As the Bustel use the manual system, it has difficulty where the customer faced a problem on package identification. Therefore, the system decided to build the website that have the additional of package identification system with DSS features which assists the guest in making choice for the suitable package before proceeding to reservation online. The research objective was to identify and to gather the data of business process, To design the system with additional of Decision Support System (DSS) features and to validate the system after the system have been designed. This research have study on several common existing hotel websites and also have study on the other website that applied the DSS features. This research also discussed on the approach and methodology used to ensure the project are complete. The methodology used was derived from SDLC Prototype Methodology. This methodology contain about three phases which are Initial Requirement, Design, and Development. Accordingly, if this system has successfully completed all phases of the methodology used in this project expectantly this system will run smoothly and completed according to specification in the requirements.